2015
DOI: 10.1002/pssa.201532838
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous alumina thin films deposited on titanium: Interfacial chemistry and thermal oxidation barrier properties

Abstract: bilayer stacks are used as model systems to investigate the role of atomic layer deposition (ALD) and chemical vapor deposition (CVD) to prepare 30-180 nm thick amorphous alumina films as protective barriers for the medium temperature oxidation (500-600 8C) of titanium, which is employed in aeronautic applications. X-ray diffraction (XRD), transmission electron microscopy (TEM) with selected area electron diffraction (SAED), and X-ray photoelectron spectroscopy (XPS) results show that the films produced from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Assuming the results by Rath et al . that larger number of oxygen vacancies promotes the ART, it is clear that the Al 2 O 3 coating within our TiO 2 nanotube layers influences the number of oxygen vacancies as it possesses a barrier against the oxygen diffusion . For example, the thickest Al 2 O 3 coating (42 nm) hinders the oxygen diffusion most significantly from all used coatings in this work, leads to highest number of oxygen vacancies within TiO 2 nanotubes, and boosts the ART process that ends up with the highest rutile content.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Assuming the results by Rath et al . that larger number of oxygen vacancies promotes the ART, it is clear that the Al 2 O 3 coating within our TiO 2 nanotube layers influences the number of oxygen vacancies as it possesses a barrier against the oxygen diffusion . For example, the thickest Al 2 O 3 coating (42 nm) hinders the oxygen diffusion most significantly from all used coatings in this work, leads to highest number of oxygen vacancies within TiO 2 nanotubes, and boosts the ART process that ends up with the highest rutile content.…”
Section: Resultssupporting
confidence: 50%
“…Assuming the results by Rath et al 43 that larger number of oxygen vacancies promotes the ART, it is clear that the Al 2 O 3 coating within our TiO 2 nanotube layers influences the number of oxygen vacancies as it possesses a barrier against the oxygen diffusion. 50 For example, the thickest Al 2 O 3 coating (42 nm) hinders the oxygen diffusion most significantly from all used coatings in this work, leads to highest number of oxygen vacancies within TiO 2 nanotubes, and boosts the ART process that ends up with the highest rutile content. In contrast, the oxygen diffusion into TiO 2 takes place more easily through thinner Al 2 O 3 coatings (1 and 10 nm), resulting in a lower number of oxygen vacancies, retarding the ART within TiO 2 nanotubes.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…These findings were in accord with the FTIR results ( Figure 2 a), suggesting that BITC−α−CD could be completely incorporated to the CS film matrix by physical interactions. In addition, it was reported that dense and amorphous characteristics rendered alumina−based films with excellent barrier capacity against high temperature [ 44 ]. The addition of amorphous poly (lactic acid) (PLA) to the poly (butylene succinate− co −butylene adipate) film matrix endowed the composite film with enhanced gas barrier property [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Constant pass energy of 30 eV and energy steps of 0.1 eV were used for high-resolution scans. Surface erosion was realized using Ar ions accelerated at 2 keV, resulting for a-Al 2 O 3 in an erosion rate of about 0.08 nm/s [21]. The atomic concentrations were determined from photoelectron peak areas using the atomic sensitivity factors reported by Scofield, taking into account the transmission function of the analyzer.…”
Section: Materials Characterization and Testsmentioning
confidence: 99%